INCIDÊNCIA DE INTOXICAÇÕES POR PRAGUICIDAS NO PARANÁ - GABRIEL, M. M.; LOPES, M.; SILVA, E.T.; BARETA, G.M.S. (Visão Acadêmica, 2004)
A importância dos praguicidas como agente causal de intoxicações e óbitos é evidenciada pelo número de ocorrências registradas. No Brasil ocupam a terceira posição dentre os agentes responsáveis pelas intoxicações agudas. Foi realizado levantamento no Centro de Informações Toxicológicas do Paraná (CIT) e no Instituto Médico Legal do Paraná (IML-PR) das intoxicações por praguicidas no período de 10/2000 a 08/2003. Neste período o CIT recebeu 1904 notificações de intoxicações e 224 intoxicações com óbito, enquanto que o IML registrou 120 óbitos provocados por praguicidas. Nos registros do IML, foram identificadas várias classes de praguicidas, havendo incidência de carbamatos na ordem de 39,2% e entre eles o aldicarb, conhecido popularmente como chumbinho. Os resultados confirmam a situação crítica quanto ao uso inadequado de praguicidas no Estado do Paraná, indicando a necessidade de orientação ao consumidor e adequada vigilância sanitária quanto ao uso e comercialização dos mesmos. INCIDENCE OF PESTICIDE POISONING IN PARANA STATE Abstract The importance of the pesticide as causal agent of intoxication and deaths is clearly shown by the number of registered cases. In Brazyl the pesticide are the third more important group of substances responsible for acute intoxication. A search for pesticide poisoning was made in the Parana States Poisoning Information Center and in the Institute for Legal Medicine from October, 2000 through August, 2003. In this period the Poisoning Information Center received 1,904 poisoning notifications and 224 poisoning cases with death. In the same period, the Institute for Legal Medicine recorded 120 deaths caused by pesticides. In the Institute for Legal Medicines file records it was found that the carbamates pesticides contributed with 39,2% of those fatal cases, being the Aldicarb (popularly known in Brazil as bullets) the main toxicological agent. The situation in Parana State is a critical one if it is taken into consideration that the use of pesticides by the population at large is made in a indiscriminate way and without the appropriate vigilance by the sanitary authorities.